2015
DOI: 10.1016/j.molonc.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33 predicts poor prognosis and promotes ovarian cancer cell growth and metastasis through regulating ERK and JNK signaling pathways

Abstract: Epithelial ovarian cancer (EOC) is the most lethal gynecological cancer, it remains a huge challenge to understand the cellular and molecular mechanisms of the aggressive behavior of EOC cells. Here we investigated the role of an immunomodulatory cytokine IL-33 and its receptor ST2 in mediating the growth and metastasis of EOC. Our data show that both IL-33 and ST2 were highly up-regulated in EOC tumors compared with normal ovary and ovarian benign tumors, and the expression levels were further increased in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 44 publications
2
80
1
Order By: Relevance
“…In support of this notion, IL33 administration promotes tumorigenesis (10, 16), and soluble ST2 is correlated with tumor burden (14, 39). IL33 predicts poor prognosis, promotes ovarian cancer cell growth and metastasis (40), and activates tumor stroma to promote intestinal polyposis (41). Our bioinformatics and pathologic analyses have demonstrated that the expression of tumor IL33 is associated with poor survival in patients with metastatic colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, IL33 administration promotes tumorigenesis (10, 16), and soluble ST2 is correlated with tumor burden (14, 39). IL33 predicts poor prognosis, promotes ovarian cancer cell growth and metastasis (40), and activates tumor stroma to promote intestinal polyposis (41). Our bioinformatics and pathologic analyses have demonstrated that the expression of tumor IL33 is associated with poor survival in patients with metastatic colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that aberrant Wnt/JNK signaling may initiate and stimulate the development of malignant phenotypes through effects on cell proliferation, survival, polarity, invasion and metastasis (Fig. 1C) (29,30). …”
Section: Introductionmentioning
confidence: 95%
“…Aberrant Wnt/β-catenin, Wnt/JNK and Wnt/Ca 2+ signaling has been associated with increasing ovarian cancer grade and poor survival (21,27,29). However, to the best of our knowledge, the relationship between these signaling pathways and ovarian cancer cisplatin chemoresistance has not yet been investigated (23,29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research demonstrated that the adherence and migratory potentials of ovarian cancer cells were significantly reduced when the FAK/STAT1 signaling pathway was inhibited by fludarabine [41] . Through regulating ERK and JNK signaling pathways, IL-33/ST2 axis were closely associated with poor prognosis of epithelial ovarian cancer patients, and further promoted ovarian cancer growth and metastasis [42] . Multicellular organismal process was probably related to human ovarian multicellular spheroid model.…”
Section: Bp Of Go Termsmentioning
confidence: 98%